Soft errors in commercial off-the-shelf static random access memories. (12th December 2016) - Dilillo, L; Tsiligiannis, G; Gupta, V; Bosser, A; Saigne, F; Wrobel, F
Abstract: This article reviews state-of-the-art techniques for the evaluation of the effect of radiation on static random access memory (SRAM). We detailed irradiation test techniques and results from irradiation experiments with several types of particles. Two commercial SRAMs, in 90 and 65 nm technology nodes, were considered as case studies. Besides the basic static and dynamic test modes, advanced stimuli for the irradiation tests were introduced, as well as statistical post-processing techniques allowing for deeper analysis of the correlations between bit-flip cross-sections and design/architectural characteristics of the memory device. Further insight is provided on the response of irradiated stacked layer devices and on the use of characterized SRAM devices as particle detectors.